Nappes in the internal zone of the northern Labrador Trough: Evidence for major early, NW-vergent basement transport - Moorhead, James; Hynes, Andrew (Geoscience Canada, 1990)
The westernmost hinterland zone of the northern Labrador Trough is characterized by four NW-trending, Archean basement bodies overlain by an upward-coarsening, amphibolite-facies volcanosedimentary cover sequence correlative with the Kaniapiskau Supergroup of the Labrador Trough. Two of the gneissic basement bodies occur in antiformal cores, but two occur in the cores of synforms. The synformal gneisses are thought to represent the down folded lower limb of a single, basement-cored nappe floored by a large thrust that roots down into one of the basement domes. The history of this area during the Hudsonian Orogeny involved initial westerly imbrication and transport of the cover succession along a thin décollement zone at the basement-cover interface. This was followed by NW-directed, basement-involved thrusting and associated folding, and large-amplitude, up-right to SW-vergent, SE-plunging folding. The NW-vergent, basement-involved event appears to be restricted to this portion of the hinterland zone.